Physcomitrella patens as a model organism in experimental plant biology - Zvanarou, Siarhej N.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2019)
This paper summarizes the anatomical, morphological, molecular and physiological characteristics of moss Physcomitrella patens, which is the most important plant model object among the non-angiosperm species. During eighty year use of P. patens in plant experimental biology, a number of fundamental discoveries have been made. Studies carried out using this plant model demonstrated new mechanisms of plant cell growth, development, DNA stability, resistance to abiotic and biotic stresses. This paper also describes the potential of the P. patens-based applications in biotechnology and discusses examples of successful works with P. patens as a biotechnological object. The perspectives for further work based on the model system of P. patens are critically evaluated.